A long cycle life, high coulombic efficiency iron molten air battery. Issue 3 (22nd March 2017) - Cui, Baochen; Xiang, Wei; Liu, Shuzhi; Xin, Hongyu; Liu, Xianjun; Licht, Stuart
Abstract : Despite the recent advancements in iron molten air batteries, great challenges still remain to realize cycling stability, high energy efficiency and a long-term cycling life. Abstract : Despite the recent advancements in iron molten air batteries, great challenges still remain to realize cycling stability, high energy efficiency and a long-term cycling life. Herein, we demonstrate a new iron molten air battery for large-scale energy storage. We replace the KCl–LiCl–LiOH eutectic electrolyte used in our previous study with a Li0.87 Na0.63 K0.50 CO3 eutectic electrolyte with added NaOH and LiOH. A fin air electrode configuration is designed to improve the coulombic efficiency. Cycling tests for the iron molten air battery showed a stable performance through 450 cycles with nearly 100% coulombic efficiency and an average discharge potential of ∼1.08 V when charged at a constant current of 0.05 A and discharged over a constant 100 Ω load to a 0.7 V cutoff at 500 °C. Moreover, the iron molten air battery had an excellent high-rate response up to 6.4C with a high coulombic efficiency of 95.1%. These results provide critical advances in developing iron molten air batteries with high efficiency and a long-term service life.